Building Information Modeling and assessing and prioritizing lack of its applicability in Iranian construction industry - Ervin Manghasarian; Mohammadali Nekooie (مهندسی و مدیریت ساخت)
Modern methods of implementing construction projects to improve quality, reduce time and thus reduce costs have always been the consideration of construction engineers and stakeholders in the project. One of these is BIM (Modern Building Information Modeling Techniques). The purpose of this study is to investigate and analyze the modeling of building information (BIM) and prioritize factors affecting the challenge of establishing this system in the country. For this purpose, determining the failure factors in the implementation of building information modeling system according to experts and experts, and by means of a questionnaire, weight and importance of these factors were determined using the ANP model and the factors were prioritized. The results showed that according to the experts' opinions and according to the binary comparison, the main criteria of the study showed that most of the factors that lead to the failure of BIM to be implemented in civil engineering projects include technical, financial, human resources and time, respectively. Other results showed that the following four subscales of information dispersion and the absence of a system with a weight of 0.2277, complex program space with a weight of 0.1634, high design cost with BIM software with a weight of 0.1578, and the need for different office staffs for a project with a weight of 0.1352 Respectively, have the most importance and therefore have the greatest impact in prioritizing the factors of non-fulfillment of BIM. By identifying the effective causes of the BIM's failure to meet the challenges, preventive measures can be taken to prevent such projects from being broken down and put them in the path to success. Considering the factors that prevented BIM from being implemented in civil engineering projects, it can be stated that modeling of building information in civil engineering projects requires the support of senior executives from its implementation, which is also dependent on the reasons mentioned above. Because it can be used by administrators to address the obstacles they face in order to manage resources and time efficiently, and so on.